An initial classification of neotropical water mites (Acari: Hydrachnidia) based on habitat preferences - Fernandez, Hugo Rafael (2011)
Existing classifications of benthic and interstitial freshwater invertebrates are described and discussed. A classification is proposed for southern neotropical (south of latitude S 15) water mites in relation to their life style and habitat preferences. The classification includes planktonic, superficial, benthic, thermal, and subterranean forms. The diversity of the Hydrachnidia family and genera (22 families, 97 genera, and 521 species) is then analyzed using the new classification. Ubiquitous stygobites deserve special consideration because they move through ecotone zones and tolerate extreme conditions. Water mite communities from a north-western Argentinean stream were first described using a surber net and consequently considered as benthic. Nineteen Hydrachnidia species (from benthic to stygobite) were collected and classified. The vertical distribution observed during the year confirmed the permanent presence of benthic Hydrachnidia, even during the first flood, which is of special importance in running waters. The functional classification we propose will facilitate comparison of fauna from different areas that have different faunistic composition but may have similar functional distribution.